Liraglutide safety and efficacy in patients with non-alcoholic steatohepatitis (LEAN): a multicentre, double-blind, randomised, placebo-controlled phase 2 study - Armstrong, Matthew James; Gaunt, Piers; Aithal, Guruprasad P.; Barton, Darren; Hull, Diana; Parker, Richard; Hazlehurst, Jonathan M.; Guo, Kathy; Abouda, George; Aldersley, Mark A.; Stocken, Deborah; Gough, Stephen C.; et al. (Elsevier, 2015)
Background